Microbiome in Oral Squamous Cell Carcinoma: Mechanisms and Signaling Pathways - Nurani Hayati; Caesary Cloudya Panjaitan; Ferry Sandra (Cell and BioPharmaceutical Institute, 2020)
Oral squamous cell carcinoma is part of head and neck squamous cell carcinoma which is the ultimate cause of morbidity and mortality in cancer. The alteration of microbial community in the saliva might act as a helpful marker for the prediction, detection and prognosis oral cancer, particularly the transition of cancer precursor lesion. There are three mechanisms of action of oral microbiota in cancer pathogenesis, chronic inflammation of bacterial stimulation, carcinogenesis by cytoskeletal rearrangements, and carcinogenic substances that produced by microorganisms. Changes in the composition of microbiota could therefore have the potential to be used as a significant oral biomarker to predict the pathological transition from oral epithelial precursor lesion to cancer.Keywords: microbiome, oral cancer cellular proliferation, microorganism, oral cancer, oral squamous cell carcinoma